If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1-2k+6k=-3+6k-8+4k
We move all terms to the left:
1-2k+6k-(-3+6k-8+4k)=0
We add all the numbers together, and all the variables
-2k+6k-(10k-11)+1=0
We add all the numbers together, and all the variables
4k-(10k-11)+1=0
We get rid of parentheses
4k-10k+11+1=0
We add all the numbers together, and all the variables
-6k+12=0
We move all terms containing k to the left, all other terms to the right
-6k=-12
k=-12/-6
k=+2
| 3x-12/3=-6 | | 9p^2−56p+12=0 | | d+7=-15 | | -9h-6=-2-10h | | 3x-5=2x-4=21 | | a=a-30+a-50 | | d/5+7=-3 | | 23=-4x-24x | | (3x-12)=-6 | | 5/2x+1/2x=117/2x | | 20=5(2p-1)+5(6p-7) | | -7f-6=10-9f | | -5x^2+22x-8=0 | | (7x-24)+(5x+14)=180 | | -8u=-10-6u | | 5n-12=3n+4* | | 0.5x-0.5(2-x)=3(4-5x)-1x | | f(4)=7(4)-3 | | 2x–5=-7 | | C(x)=36x+1,500 | | 4x=10x-4 | | x+49+71=70 | | 3-5(9-w)=2(w+4)+1 | | 90=x+21 | | 0.50x+.35=28.5 | | -8r-3=-7r-10 | | 7j=-6+j | | 2r+8(5r-6)=14-7r | | (14x+36)=180 | | 97=-(6n-5)-8 | | 5t-105=-10 | | 5f=–6+6f |